2018
DOI: 10.1111/rda.13363
|View full text |Cite
|
Sign up to set email alerts
|

Fertility of lactating dairy cows inseminated with sex‐sorted or conventional semen after Ovsynch, Presynch–Ovsynch and Double‐Ovsynch protocols

Abstract: ContentsThe objective was to compare pregnancy per artificial insemination (P/AI) with conventional (CS) or sex-sorted semen (SS) in dairy cows subjected to one of the three timed AI protocols. Cows (n = 356) were randomly assigned to synchronization with Ovsynch (OVS), Presynch-Ovsynch (PO) or Double-Ovsynch (DO) and inseminated on Day 77 ± 3 postpartum with either frozen-thawed SS (n = 182) or CS (n = 184) of the same bull. More cows were cyclic at the beginning of breeding Ovsynch increased (p < 0.01) with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
8
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 21 publications
3
8
0
1
Order By: Relevance
“…In the present study, the sMPO programme was associated with a higher probability of pregnancy per AI after the first AI than Ovsynch or AI following oestrus detection, and those associated with Ovsynch and AI following oestrus detection did not differ. These findings are consistent with those of previous studies showing that the Presynch-Ovsynch and Double-Ovsynch programmes are associated with superior first AI pregnancy rates to Ovsynch (Karakaya-Bilen et al, 2018;Navanukraw et al, 2004) or AI following oestrus detection (Santos et al, 2017). The overall pregnancy rate of 46.2% 45 days after the first TAI in the sMPO group that was obtained in the present study TA B L E 3 Factors affecting the probability of pregnancy per AI 30 and 45 days after the first TAI in the sMPO group, identified using a logistic regression model The intervals between the first and second treatments during pre-synchronization.…”
Section: The Probability Of Pregnancy By 105 Days Postpartumsupporting
confidence: 93%
“…In the present study, the sMPO programme was associated with a higher probability of pregnancy per AI after the first AI than Ovsynch or AI following oestrus detection, and those associated with Ovsynch and AI following oestrus detection did not differ. These findings are consistent with those of previous studies showing that the Presynch-Ovsynch and Double-Ovsynch programmes are associated with superior first AI pregnancy rates to Ovsynch (Karakaya-Bilen et al, 2018;Navanukraw et al, 2004) or AI following oestrus detection (Santos et al, 2017). The overall pregnancy rate of 46.2% 45 days after the first TAI in the sMPO group that was obtained in the present study TA B L E 3 Factors affecting the probability of pregnancy per AI 30 and 45 days after the first TAI in the sMPO group, identified using a logistic regression model The intervals between the first and second treatments during pre-synchronization.…”
Section: The Probability Of Pregnancy By 105 Days Postpartumsupporting
confidence: 93%
“…Surprisingly, the P/AI of heifers starting the ovulation protocol in the proestrus, however, was not different than the P/ AI of heifers starting the protocol at other stages of the estrous cycle. In a recent experiment, Karakaya-Bilen et al (2019) demonstrated that presynchronization of heifers with PGF 2α 10 d before the start of the ovulation synchronization protocol improves P/AI largely because of increased ovulation to the first GnRH injection of the protocol and perhaps because of improved ovulation at the end of the protocol. Our findings suggest that ovulation synchronization protocols for fixed time AI for heifers should not be initiated between d 10 and 17 of the estrous cycle.…”
Section: Abmentioning
confidence: 99%
“…Sex is a genetic trait long sought after by the dairy industry because of the importance of females for production of milk and cash flow (Seidel, 2003). The development of sex-sorting technologies has resulted in wide adoption of sex-sorted semen in the dairy industry, despite the reduced pregnancy per artificial insemination (P/AI) of cattle inseminated with sexsorted semen (DeJarnette et al, 2010;Karakaya-Bilen et al, 2019). The reduced P/AI with sex-sorted semen is believed to be a consequence of the reduced inseminating dose compared with conventional semen and changes to sperm viability that occur during the sorting process (Carvalho et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Development of fertility programs for lactating dairy cows increased both service rate and P/AI to timed artificial insemination (TAI) compared with a detected estrus (Santos et al, 2017). Use of sexed semen in lactating dairy cows, particularly primiparous cows that have higher fertility and more advanced genetics than multiparous cows, is now increasing on dairy farms; however, fertility of lactating dairy cows inseminated using sexed semen remains less than that using conventional semen (Karakaya-Bilen et al, 2019). Delayed insemination with sexed semen relative to the onset of increased physical activity associated with estrus increased the P/AI of Jersey cows (Bombardelli et al, 2016;Nebel 2018).…”
Section: Short Communicationmentioning
confidence: 99%